2015
DOI: 10.3329/bjb.v43i2.21673
|View full text |Cite
|
Sign up to set email alerts
|

The breeding system and reproductive ecology of the endangered plant Fagopyrum dibotrys (D. Don) Hara

Abstract: Distyly has been confirmed in Fagopyrum dibotrys (D. Don) Hara. The species are dimorphic in style length, anther height, pollen size and number but not in flower diameter, pollen surface ornamentation and stigma papilla cells. In F. dibotrys populations, style-morph ratios vary from isoplethy (1L : 1S) to strongly L-biased, or they more often contain only the L-morph. Moreover, it was found that larger isoplethic populations of F. dibotrys could produce more seeds than smaller single-morph populations. F. dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Both distyly and homostyly have been noted in previous studies of Fagopyrum (Darwin, 1877; Ohnishi, 1989; Ohnishi and Matsuoka, 1996; Nishimoto et al, 2003; Liu et al, 2008; Shao et al, 2011), but quantification of the reproductive system involved only the large‐achene group of buckwheat that includes F. dibotrys (Chen et al, 2014) and F. esculentum (Samborska‐Ciania et al, 1989; Björkman, 1995; Cawoy et al, 2006), while floral traits in F. tataricum and the small‐achene group of buckwheat have not before been examined. Compared to six species in the small‐achene group, flowers of the large‐achene group were significantly larger (test of corolla diameter, Wald χ 2 = 873.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Both distyly and homostyly have been noted in previous studies of Fagopyrum (Darwin, 1877; Ohnishi, 1989; Ohnishi and Matsuoka, 1996; Nishimoto et al, 2003; Liu et al, 2008; Shao et al, 2011), but quantification of the reproductive system involved only the large‐achene group of buckwheat that includes F. dibotrys (Chen et al, 2014) and F. esculentum (Samborska‐Ciania et al, 1989; Björkman, 1995; Cawoy et al, 2006), while floral traits in F. tataricum and the small‐achene group of buckwheat have not before been examined. Compared to six species in the small‐achene group, flowers of the large‐achene group were significantly larger (test of corolla diameter, Wald χ 2 = 873.…”
Section: Discussionmentioning
confidence: 79%
“…2). Our results are consistent with those of previous studies in that there was no difference found in corolla diameter between morphs of the distylous taxa, and stigma height and pollen number were greater in L‐morphs than in S‐morphs, while anther height, stigma‐anther distance, and pollen size were larger in S‐morphs than in L‐morphs in F. dibotrys and F. esculentum (except for corolla diameter in F. esculentum ) (Samborska‐Ciania et al, 1989; Björkman, 1995; Cawoy et al, 2006; Chen et al, 2014). Corolla diameter was observed to be smaller in L‐morphs compared with the S‐morphs in F. esculentum , a feature that may vary depending upon the particular cultivar of this domesticated species.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of records were identified to genus level as Fagopyrum . Chinese palynological work predominantly uses the reference criteria of Wang et al ( 1995 ); Zhou et al ( 2003 ) and Chen et al ( 2014 ). These authors consider that Fagopyrum pollen cannot be identified to species based on size, shape or surface ornamentation.…”
Section: Discussionmentioning
confidence: 99%
“…All four traditionally recognized species of the Cymosum group are morphologically well-defined. Fagopyrum homotropicum and F. tataricum are self-compatible with homostylous flowers whereas F. cymosum and F. esculentum are self-incompatible with distylous flowers ( Ohnishi and Matsuoka, 1996 ; Fesenko et al., 2006 ; Chen et al., 2014 ; Ohsako and Li, 2020 ). Fagopyrum cymosum is a perennial herb that is sometimes utilised as a forage crop and also for medicinal purposes ( Prakash and Yadav, 2016 ), whereas other three species are annuals.…”
Section: Introductionmentioning
confidence: 99%